Control of Taenia solium; A Case for Public and Private Sector Investment - Thomas, Lian F.; Cook, E. Anne J.; Fèvre, Eric M.; Rushton, Jonathan (Frontiers in Veterinary Science, 2019)
The zoonotic helminth T. solium is one of the leading causes of acquired epilepsy in endemic countries, resulting in a high burden both in human health and social stigma of affected people [1; 2; 3]. In 2012 T. solium was highlighted as a priority for control in the World Health Assembly resolution 66.12 [4]. Despite a call for validated control strategies by 2015 and a ‘Tool Kit’ of control options being available, relatively few examples of successfully implemented and sustainable control programs are available [5; 6; 7]. A minimal control strategy focusing solely on the porcine host has also been proposed although the cost-effectiveness of such has yet to be explored [8]. Although acknowledgement has been made of the need for initiatives to be sustainable, we are yet to see sufficient consideration of the balance between the provision of public and private goods, and the need for engagement of the people and organisations in the pork value chains within T. solium control strategies. We utilised a food chain risk analysis model to determine the incremental cost-effectiveness ratio (ICER) in terms of $/infective meal avoided, of combining a pharmaceutical intervention in pigs with strengthened meat hygiene services. The addition of a vaccination and treatment protocol, at an additional 10.3% cost, was illustrated to have the potential to improve the ICER of improving meat inspection by 74.6%. The vaccination and treatment protocol also had the potential to reduce the losses borne by the pork industry of condemned meat by 66%, highlighting the potential to leverage private sector investment in T. solium control.